Fabrication of 3D Biomimetic Microfluidic Networks in Hydrogels. Issue 17 (30th May 2016) - Heintz, Keely A.; Bregenzer, Michael E.; Mantle, Jennifer L.; Lee, Kelvin H.; West, Jennifer L.; Slater, John H.
Abstract : A laser‐based hydrogel degradation technique is developed that allows for local control over hydrogel porosity, fabrication of 3D vascular‐derived, biomimetic, hydrogel‐embedded microfluidic networks, and generation of two intertwining, yet independent, microfluidic networks in a single construct.